(untitled) (Journal of Nepal Geological Society, 2025)
This study aims to determine the distribution and potential ecological risk of heavy metals and to identify the possible sources of heavy metal contamination in the surface sediments of the Bagmati River in Kathmandu, Nepal. The sediment samples were analyzed for their pH, electrical conductivity (EC), organic matter (OM), texture, and heavy metal concentration of Cu, Zn, Cd, and Pb. Various indices such as contamination factor (CF), geoaccumulation index (Igeo), modified degree of contamination (mCd), pollution load index (PLI), and potential ecological risk index (RI) were calculated to assess the risk of heavy metals. The sediment exhibited a slightly alkaline pH, with significant variation in EC along different river sections. The OM levels were moderate in the upstream and high in the middle and downstream. The sediment was predominantly sandy and loamy sandy in composition. The concentration of Pb was below the limit of detection (<0.01 μg/g) in all sediment samples. The ecological risk associated with Cu, Zn, and Cd in the sediment is categorized as low to moderate based on the RI. The HCA indicates that the upstream has less heavy metal pollution than the middle and downstream sections. There are significant positive correlations between Cu, Zn, and Cd in terms of their concentration. The PCA suggests anthropogenic activities, such as the mixing of municipal and domestic sewage, hospital waste, and industrial activities, may serve as sources of heavy metals in the river sediment. It is necessary to regularly monitor the sediment and water of Bagmati River to identify the sources of heavy metal pollution and record changes in the level of contamination.